Modern sales management - Okeke, C. I. (Lagos, Nigeria : Everlead Printing & Publishing Co., 1993)
Presents modern concepts, principles, processes and practices in salesmanship and sales management that helps to excel in all forms of freeexchange interactions.
Includes bibliographical references.
oif 26/02/15
Loan
Keywords: Sales management; Marketing